Impact of a fire burn on solar irradiance and PV power. (April 2015) - Perry, Matthew; Troccoli, Alberto
Highlights: Sky camera images document the cloudless sky conditions and the development of a smoke plume from fire burns. Direct normal irradiance was reduced by up to 32% compared to clear sky equivalent. Smoke had the most impact in the spectral wavelength range from 400 to 500 nm. Solar photovoltaic power from a 1.56 kW system was reduced by up to 27% compared to clear sky equivalent. Abstract: Aerosols produced by fire burns can have marked impacts on PV power production. Here we take advantage of an isolated, short-lived but well monitored fire burn event during an otherwise clear sky day – a case of a serendipitous 'earth experiment' – to study its impact on both solar irradiance and solar power recorded at the nearby solar lab. The local council controlled burns happened at Black Mountain in Canberra, Australia. Evidence from the solar lab sky-camera images was used to confirm that the sky was clear of clouds during the late afternoon of 4th March 2014 so that the effect of the smoke plume could be isolated, and to observe the development of the plume. Global and direct irradiance observations were compared with those from analogous clear days, as well as with values obtained from a clear sky model, in order to estimate the reduction in irradiance due to the smoke plume. The results showed that global irradiance was reduced by 6.5% and direct irradiance by 9% during a 140 min afternoon period, with one-minute reductions of up to 26% and 32% respectively. The spectral global irradiance showed that the smoke had the greatest impact in the wavelength range from 400 to 500 nm. A spectral analysis of the impact of smoke on six different PV technologies revealed that the least impact was on the mono-silicon cells used in this study. The resulting effect of solar power output was an overall reduction of 7% during the study period and a peak reduction of 27%.